Pengaruh Supervisi dan Quality of Work Life (QWL) terhadap Motivasi Kerja Guru SMPN Kota Baru Kabupaten Timor Tengah Utara Provinsi Nusa Tenggara Timur - Yuni Cynthia Dewi Tjandring; Sedarmayanti Sedarmayanti; Dety Mulyanti (EduInovasi: Journal of Basic Educational Studies, 2025)
Academic supervision has a positive influence on teacher work motivation. Effective supervision can improve teacher competence, which in turn can increase their motivation to teach. The relationship between Quality of Work Life is measured by employee participation, being given the opportunity to develop a career, being given the opportunity to resolve conflicts, having a good communication space between subordinates and superiors and fellow co-workers, a work environment that ensures health and safety and work security, getting appropriate rewards and creating pride. Teacher Quality of Work Life (QWL) refers to the pleasant or unpleasant conditions of the work environment for a teacher, which includes various aspects such as appreciation, security, working conditions, interpersonal relationships, and intrinsic meaning in work. Good QWL can improve teacher performance and contribute to job satisfaction and organizational commitment. This study is based on the gap in teacher work motivation so that the research problem is formulated, namely how do supervision and quality of work Life (QWL) affect the work motivation of teachers at SMPN Kota Baru, North Central Timor Regency, East Nusa Tenggara Province? This study aims to determine the effect of supervision and quality of work Life (QWL) on the work motivation of teachers at SMPN Kota Baru, North Central Timor Regency, East Nusa Tenggara Province. This study uses a survey method with a quantitative approach using verification analysis. The study was conducted at SMPN Kota Baru, North Central Timor Regency, East Nusa Tenggara Province, namely on 37 teachers. Data collection was carried out using a questionnaire which was carried out from May 23 to June 23, 2025. Work motivation of teachers of SMPN Kota Baru, North Central Timor Regency, East Nusa Tenggara Province with a good category. The results of this study explain that: the implementation of academic supervision on teachers of SMPN Kota Baru, North Central Timor Regency, East Nusa Tenggara Province has been running well. Quality of work life (QWL) on teachers of SMPN Kota Baru, North Central Timor Regency, East Nusa Tenggara Province with a good category. there is a significant influence between academic supervision on teacher work motivation, tcount 2.041> ttable. There is a significant influence between price on teacher work motivation, tcount 3.510> ttable = 1.691. Academic supervision and Quality of work life (QWL) simultaneously affect teacher work motivation, Sig.= 0.005 <0.05. When academic supervision and QWL go hand in hand, the impact on motivation can be more significant.